TEST-retest reliability of kinetic variables measured on campus board in sport climbers - Alvares de Campos Abreu, E.; Santos Araújo, S. R.; da Cunha Peixoto Cançado, G. H.; Pereira de Andrade, A. G.; Chagas, M. H.; Menzel, H.-J. K. (Sports Biomechanics, 2019)
Sport climbers frequently use campus board (CB) to improve their upper limb strength under similar conditions of high-difficulty sport climbing routes. The objective of this study was to assess the test-retest reliability of peak force and impulse measured using a CB instrumented with two load cells on starting holds. The same evaluator examined 22 climbers on two days with 48 h between the assessments. The participants performed five concentric lunges (CL) and five lunges with stretch-shortening cycle with 1 min intervals between repetitions and 10 min between exercises. All variables were associated with significant intraclass correlation coefficient (ICC) values (p = 0.001), and none variable showed systematic errors (p > 0.05). Peak force ICC was higher than 0.88, and the standard error of measurement (SEM%) was less than 5%. Impulse ICC for the CL was greater than 0.90, and the SEM% was less than 14%. We conclude that the kinetic variables measured using the CB were reliable. The ability of the hands to maintain contact with the holds (peak force) and the abilities of the arms and shoulders vertically move the centre of mass (impulse) should be taken into account by coaches on CB training prescription as well for further research.